The Role of Bone Marrow Mesenchymal Stem Cells and Adipose Tissue-Derived Stem Cells in the Treatment of Liver Failure: A Literature Review - Mohamed Ziedan; Maha Ayman; Dina Mohamed (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Liver disease is a major health problem that endangers human health worldwide. Stem cells have the unique ability to morph or differentiate into different types of cells within the body. In this way, stem cells can be used to seek out damaged liver tissue and regenerate the organ itself. Mesenchymal stem cells are multipotent stem cells that can self-renew and differentiate into different cell types. In other words, mesenchymal stem cells can become a variety of different cell types including adipose tissue, cartilage, muscle, tendon/ligament, bone, neurons, and hepatocytes. Many studies have shown that Mesenchymal stem cells play an essential role in liver recovery, and further research has verified the preliminary effectiveness and safety of these therapies. types of liver disease that are most suitable for MSC application should be determined, and the preparation and engraftment of MSCs should be standardized. Stem cell-based therapies will emerge as an effective treatment strategy for liver diseases in now and the future. Researchers conduct an examination of articles that are in accordance with the issue to be studied. Articles used in literature review are obtained through the database of international journal providers through PubMed, we investigated six clinical studies and discussed what happened in these clinical studies and the extent of the effectiveness of stem cells in treatment and whether the degree of liver disease had a role in the effectiveness of stem cells, we also discussed the mechanism of stem cells in treatment. One of six articles proved that Zeaxanthin dipalmitate (ZD) could enhance the defensive abilities against adverse stresses of human adipose-derived mesenchymal stem cells, One of six articles proved that infusion of allogeneic bone marrow-derived MSCs improving liver function and decreasing the incidence of severe infections. The rest articles proved that MSCs both Bone Marrow Stem cells (BMSCs) and Adipose Derived Stem Cells (ADSCs) are promising therapeutic agents for the liver fibrosis and cirrhosis treatment. In this review, we suggest that formulating and following treatment, Further studies are needed to determine the related mechanisms to enhance MSC efficacy.